EXPLORING ETHICAL CONTINUITY: A COMPARATIVE ANALYSIS OF APOLOGY AND LETTER FROM BIRMINGHAM JAIL - Ernawati, Asih; Riyatno , Riyatno (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM Azramedia Indonesia, 2024)
This article examines the enduring relevance of Socrates'